PENGEMBANGAN BUKU CERITA BERGAMBAR DALAM PENGENALAN BULLYING PADA ANAK USIA DINI DI TK AISYIYAH BUSTANUL ATFHAL PULAU PUNJUNG - Agus Saputra, M.Pd.; Ana Novitasari,M.pd; Romi Yanti (STKIP Subang, 2025)
This research aims to develop a product, namely a Teaching ficture storybooks in introducing bullying to Early Childhood. The researcher chose picturestory books because they make it easier for educators to introduce bullying toearly childhood.This type of research is Research and Development (R&D) usingthe ADDIE development model, which consists of analysis (analyze), design,development, implementation, and evaluation stages. This research wasconducted at TK Aisyiyah Bustanul Atfhal Pulau Punjung in the 2024/2025academic year, semester 2. Data collection techniques used teacher responsequestionnaires, validation sheets, media exper and linguist.The validity results ofpicture story in introducing bullying to early childhood, which was carried out bytwo validators, obtained an average score of 91,78%, categorized as very valid.The teacher practicality results obtained a score of 86% with the category of verypractical, and the average effectiveness score obtained a score of 95.45% with thecategory of very effective. It can be concluded that the teaching picture story inintroducing bullying to early childhood, developed by the researcher is suitable foruse because it has met the criteria of being valid, practical, and effective.